Full single arch distalization in Class II malocclusion using subzygomatic temporary anchorage devices: A case report - Bandar Alyami (Wolters Kluwer Medknow Publications, 2023)
Distalization of the maxillary molars is among the most commonly employed nonextraction treatment strategies for angle Class II malocclusion. This approach is primarily recommended for subjects with dentoalveolar maxillary protrusion or minor skeletal abnormalities. A case of a 17-year-old Hispanic male patient with Class II skeletal base with Class II end on canines and molars, upper anterior crowding, severe overjet, and moderate overbite is hereby reported. He refused extraction; therefore, he was offered full single upper arch distalization using subzygomatic temporary anchorage devices (TADs). After 11 months of retraction, the TADs were removed and it was observed that the overjet and overbite were now within normal values and midline shift was also corrected. Satisfactory leveling and alignment, alleviation of crowding, and Class I molar and canine relationship were achieved. The aim of this case report was to describe full single arch distalization using subzygomatic TADs in a patient with Class II skeletal, molar, and canine relationships.